Synchronous reference frame fundamental method in shunt active power filter for mitigation of current harmonics - Musa, Suleiman; Mohd Radzi, Mohd Amran (Universiti Putra Malaysia Press, 2017)
This research presents compensation of current harmonic disturbance in power system network using shunt active power filter. In this paper, harmonic extraction using Synchronous Reference Frame Fundamental technique (SRFF) was investigated for three phase 3-wire system. It proposes a method based on direct current measurement of load currents using a band pass filter at low cut off frequencies to improve the filtering ability in highly contaminated loads. The proposed filter consists of second order low pass and high pass filters cascaded together at suitable frequencies, estimated based on the output of these units to mitigate the current harmonics. The performance of the system was simulated in Matlab Platform and evaluated considering total harmonic distortion of the source current in a three-phase balanced network. The simulation results show the ability of the proposed tracking scheme to accurately estimate harmonics.